Five Run Away Together - Blyton, Enid (London Hodder Children's Books, 2015)
When the Famous Five discover a mysterious locked trunk on Kirrin Island, they suspect that smugglers are to blame until they hear a chilling scream that leads to something more sinister
Keywords: Children's Literature - Fiction : Adventure